2017
DOI: 10.1021/acs.jpca.7b04847
|View full text |Cite
|
Sign up to set email alerts
|

Can COSMOTherm Predict a Salting in Effect?

Abstract: We have used COSMO-RS, a method combining quantum chemistry with statistical thermodynamics, to compute Setschenow constants (K) for a large array of organic solutes and salts. These comprise both atmospherically relevant solute-salt combinations, as well as systems for which experimental data are available. In agreement with previous studies on single salts, the Setschenow constants predicted by COSMO-RS (as implemented in the COSMOTherm program) are generally too large compared to experiments. COSMOTherm ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
(131 reference statements)
3
16
0
Order By: Relevance
“…Changes in the relative ratios of unhydrated and hydrated forms would be expected due to changes in the molecular interactions (water-methylglyoxal, water-water) when ions co-exist in the solution. Such phenomena have been reported in previous experimental (Waxman et al, 2015) and computational (Toivola et al, 2017) studies, which have shown decrease of the cosolubility of methylglyoxal in aqueous solutions with addition of NaCl and Na 2 SO 4 (salting out effect). Here we observe a small change in the relative intensities between the peaks A and B in pure methylglyoxal solution compared to solution spiked with Na 2 SO 4 , but the shape of the background also changed in the spectrum and thus these changes remain inconclusive.…”
Section: Feature At 290 Evsupporting
confidence: 80%
“…Changes in the relative ratios of unhydrated and hydrated forms would be expected due to changes in the molecular interactions (water-methylglyoxal, water-water) when ions co-exist in the solution. Such phenomena have been reported in previous experimental (Waxman et al, 2015) and computational (Toivola et al, 2017) studies, which have shown decrease of the cosolubility of methylglyoxal in aqueous solutions with addition of NaCl and Na 2 SO 4 (salting out effect). Here we observe a small change in the relative intensities between the peaks A and B in pure methylglyoxal solution compared to solution spiked with Na 2 SO 4 , but the shape of the background also changed in the spectrum and thus these changes remain inconclusive.…”
Section: Feature At 290 Evsupporting
confidence: 80%
“…For NAFA concentrations between 0.1 and 1 g L À1 , surface tension for a given NAFA concentration tends to decrease with increasing NaCl concentration due to salting out of NAFA by NaCl. [31][32][33][34][35][36][37][38] This trend is however not uniform over the whole composition range. In particular for surface tensions at t ¼ 0 s, a trough appears in the tting surface, possibly due to the sensitivity of the t to data points.…”
Section: Modelingmentioning
confidence: 88%
“…When the nonideality is due to interactions with inorganic compounds, which can be highly concentrated in ambient aerosol particles, the effect is called a "salting-in" (γ < 1) or "salting-out" (γ > 1) interaction, depending on whether the interaction favors or disfavors, respectively, the presence of the compound in the phase in question. The effect of salting in or salting out on chemical systems with atmospheric relevance has been assessed with both experimental and theoretical approaches (Toivola et al, 2017;Wang et al, 2014;Waxman et al, 2015;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%